The effect of starch isolation method on physical and functional properties of Portuguese nut starches. II. Q. rotundifolia Lam. and Q. suber Lam. acorns starches - Correia, Paula Reis; Nunes, Maria Cristiana; Beirão-da-Costa, Maria Luísa (Food Hydrocolloids, 2013)
A new starch was isolated from fruits of two acorn species, Quercus rotundifolia and Quercus suber by alkaline (A3S) and enzymatic (ENZ) methods and physical and functional properties were studied. The isolation method induced changes in most of those properties in the isolated starches, mainly in resistant starch content, syneresis, pasting, thermal and rheological properties. Isolated acorn starches presented high amylose content (53e59%) and resistant starch content (30.8e41.4%). Acorn starches showed limited and similar solubility values and swelling power values, showing a gradual increase from 60 C to 90 C. The pasting temperatures ranged from 67.5 to 72.0 C and pastes did not present breakdown, which is suggestive of a high paste stability of acorn starches during heating. At ambient temperature the turbidity and syneresis values were low, but when held at freezing temperatures the syneresis signiﬁ- cantly increased. Thermal analysis revealed that the acorn starches easily undergo transition phenomena as shown by the low To and enthalpy values (4.1e4.3 J/g), these effects were more evident in starches isolated by ENZ method. Pastes are more elastic than viscous and form strong gels after cooling. Q. suber starch was shown to be more sensitive to the effect of isolation method. Generally, starch isolated by enzymatic method presented less interesting functional properties, since this isolation procedure greater affected the raw structure of starches
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorns; Functional properties; isolation method; rheological properties; starch; thermal properties

Cork suberin as an additive in offset lithographic printing inks - Cordeiro, N; Blayo, A; Belgacem, N M; Gandini, A; Pascoal Neto, C; LeNest, J.-F (Industrial Crops and Products, 2000)
Suberin oligomers, isolated from cork (Quercus suber L.), were used as additives in ‘Waterless’ and vegetable-oil ink formulations, in the range of 2–10% w:w. The rheological behaviour of the suberin oligomers as well as of the inks, with and without suberin, were investigated as a function of temperature. It was shown that the addition of suberin induces a decrease of viscosity of both inks. The tack of pristine inks, suberin oligomers and their mixtures were determined at different temperatures: the variation of this parameter as a function of time provided information about the drying kinetics of these formulations. The tack of the ‘Waterless’ ink was found to increase with the introduction of suberin, whereas that of vegetable-oil based counterparts decreased. All the trends observed were interpreted in terms of the differences in composition between the two types of inks. Preliminary printing tests were carried out with the various suberin-containing inks
Keywords: Additive; Quercus suber L.; rheological properties; suberin; Tack; Vegetable oil-based ink; Viscosity; Waterless ink

Cork suberin as an additive in offset lithographic printing inks - Cordeiro, N.; Blayo, A.; Belgacem, N. M.; Gandini, A.; Pascoal Neto, C.; LeNest, J.-F. (Industrial Crops and Products, 2000)
Suberin oligomers, isolated from cork (Quercus suber L.), were used as additives in ‘Waterless’ and vegetable-oil ink formulations, in the range of 2–10% w:w. The rheological behaviour of the suberin oligomers as well as of the inks, with and without suberin, were investigated as a function of temperature. It was shown that the addition of suberin induces a decrease of viscosity of both inks. The tack of pristine inks, suberin oligomers and their mixtures were determined at different temperatures: the variation of this parameter as a function of time provided information about the drying kinetics of these formulations. The tack of the ‘Waterless’ ink was found to increase with the introduction of suberin, whereas that of vegetable-oil based counterparts decreased. All the trends observed were interpreted in terms of the differences in composition between the two types of inks. Preliminary printing tests were carried out with the various suberin-containing inks
Keywords: Additive; Quercus suber L.; rheological properties; suberin; Tack; Vegetable oil-based ink; Viscosity; Waterless ink

Cork suberin as a new source of chemicals: 2. Crystallinity, thermal and rheological properties - Cordeiro, N.; Belgacem, N. M.; Gandini, A.; Neto, C. P. (Bioresource technology, 1998)
Suberin samples, obtained by alkaline methanolysis from cork (Quercus suber L.), were submitted to various physical characterizations; DSC, TGA, optical microscopy, density and rheological properties. A sub- stantial proportion of these oligomers possessed a microcrystalline character with a melting range between 0 and 50°C. The amorphous part was liquid at room temperature and did not display a detectable glass transition upon cooling because of its wide molecular weight distribution. The viscous behaviour of suberin at room temperature was both plastic and thixotropic because of the structuring role of the micro- crystals
Keywords: Alkaline methanolysis; cork of Quercus suber L.; crystallinity; Density; rheological properties; suberin; thermal characterization

Cork suberin as a new source of chemicals: 2. Crystallinity, thermal and rheological properties - Cordeiro, N; Belgacem, N M; Gandini, A; Neto, C P (Bioresource technology, 1998)
Suberin samples, obtained by alkaline methanolysis from cork (Quercus suber L.), were submitted to various physical characterizations; DSC, TGA, optical microscopy, density and rheological properties. A sub- stantial proportion of these oligomers possessed a microcrystalline character with a melting range between 0 and 50°C. The amorphous part was liquid at room temperature and did not display a detectable glass transition upon cooling because of its wide molecular weight distribution. The viscous behaviour of suberin at room temperature was both plastic and thixotropic because of the structuring role of the micro- crystals
Keywords: Alkaline methanolysis; cork of Quercus suber L.; crystallinity; Density; rheological properties; suberin; thermal characterization